2019
DOI: 10.1007/s10570-019-02349-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of strength and stiffness improvement of paper after PFI refining with a focus on the effect of fines

Abstract: Refining (i.e., mechanical beating of pulp) is a common procedure that is used in paper-making to improve the mechanical properties of the final product. The improvements caused by refining are mainly attributed to increased density and to a better bonding between fibers. In this work, we study how various mechanisms that can be triggered by refining affect the tensile behavior of the sheets. Consequently, we use direct numerical simulations of fiber networks. We relate our finding to the experimental measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 28 publications
(13 reference statements)
0
47
0
Order By: Relevance
“…At equivalent energies, microfibre additions to primary pulp yielded higher bulk compared to multistage LC refining. Increased fibre flexibility induced by refining, as well as higher specific surface due to fibre cutting, fibrillation and generation of fines during the refining process promote inter-fibre bonding (Gorski et al 2012;Kerekes and Tam Doo 1985;Page 1989;Seth 2003) and lead to fibre network collapse and reduction of bulk (Forgacs 1963;Motamedian et al 2019;Retulainen et al 1993). Microfibre composites, on the other hand, were prepared by mixing long and intact fibres of primary pulp with a relatively small amount of highly developed fines and fibrils; this resulted in open construction handsheets with relatively higher bulk and improved mechanical strength.…”
Section: Pulp Freenessmentioning
confidence: 99%
“…At equivalent energies, microfibre additions to primary pulp yielded higher bulk compared to multistage LC refining. Increased fibre flexibility induced by refining, as well as higher specific surface due to fibre cutting, fibrillation and generation of fines during the refining process promote inter-fibre bonding (Gorski et al 2012;Kerekes and Tam Doo 1985;Page 1989;Seth 2003) and lead to fibre network collapse and reduction of bulk (Forgacs 1963;Motamedian et al 2019;Retulainen et al 1993). Microfibre composites, on the other hand, were prepared by mixing long and intact fibres of primary pulp with a relatively small amount of highly developed fines and fibrils; this resulted in open construction handsheets with relatively higher bulk and improved mechanical strength.…”
Section: Pulp Freenessmentioning
confidence: 99%
“…While for secondary fines their effect on strength properties has extensively been reported by several researchers, this is not the case for primary fines, where only a few studies are available focusing on the effects of their removal or addition on paper technological properties (Bäckström et al 2008;Chauhan et al 2012;Ferreira et al 1999Ferreira et al , 2000Mayr et al 2017b;Motamedian et al 2019). Due to the differences in experimental designs, these studies did not always show consistent results.…”
Section: Introductionmentioning
confidence: 97%
“…In order to improve the strength properties of paper it is necessary to increase the relative bonded area and/ or specific bonding strength (Dasgupta 1994;Motamedian et al 2019). This increase can be achieved by sheet densification, which is positively influenced by addition of fine cellulosic materials such as micro or nanofibrillated celluloses or pulp fines, therefore leading to an increase in tensile properties (Bäckström et al 2008;Taipale et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LC refining would make it possible to produce more fibrillar fines also called secondary fines (Odabas et al 2016) and thereby further increase the network strength at maintained bulk (Ljungqvist et al 2014. Also Motamedian et al (2019) found that an increased number of fibrillar fines increases the strength of paper. This was explained by the ability of fibrillar fines to reinforce the bonds in the fibre network.…”
Section: Introductionmentioning
confidence: 97%